Proteasome inhibition as a therapeutic approach in atypical teratoid/rhabdoid tumors. Issue 1 (14th April 2020) - Morin, Andrew; Soane, Caroline; Pierce, Angela; Sanford, Bridget; Jones, Kenneth L; Crespo, Michele; Zahedi, Shadi; Vibhakar, Rajeev; Mulcahy Levy, Jean M
Abstract: Background: Atypical teratoid/thabdoid tumor (AT/RT) remains a difficult-to-treat tumor with a 5-year overall survival rate of 15%–45%. Proteasome inhibition has recently been opened as an avenue for cancer treatment with the FDA approval of bortezomib (BTZ) in 2003 and carfilzomib (CFZ) in 2012. The aim of this study was to identify and characterize a pre-approved targeted therapy with potential for clinical trials in AT/RT. Methods: We performed a drug screen using a panel of 134 FDA-approved drugs in 3 AT/RT cell lines. Follow-on in vitro studies used 6 cell lines and patient-derived short-term cultures to characterize selected drug interactions with AT/RT. In vivo efficacy was evaluated using patient derived xenografts in an intracranial murine model. Results: BTZ and CFZ are highly effective in vitro, producing some of the strongest growth-inhibition responses of the evaluated 134-drug panel. Marizomib (MRZ), a proteasome inhibitor known to pass the blood–brain barrier (BBB), also strongly inhibits AT/RT proteasomes and generates rapid cell death at clinically achievable doses in established cell lines and freshly patient-derived tumor lines. MRZ also significantly extends survival in an intracranial mouse model of AT/RT. Conclusions: MRZ is a newer proteasome inhibitor that has been shown to cross the BBB and is already in phase II clinical trials for adult high-grade glioma (NCT NCT02330562 and NCT02903069). MRZ strongly inhibits AT/RT cell growth both in vitro and in vivo via a moderately well-characterized mechanism and has direct translational potential for patients with AT/RT.